TADs and Their Borders: Free Movement or Building a Wall?. Issue 3 (7th February 2020) - Chang, Li-Hsin; Ghosh, Sourav; Noordermeer, Daan
Abstract: The tridimensional (3D) organization of mammalian genomes combines structures from different length scales. Within this organization, Topologically Associating Domains (TADs) are visible in Hi-C heat maps at the sub-megabase scale. The integrity of TADs is important for correct gene expression, but in a context-dependent and variable manner. The correct structure and function of TADs require the binding of the CTCF protein at both borders, which appears to block an active and dynamic mechanism of "Cohesin-mediated loop extrusion." As a result, mammalian TADs appear as so-called "loop domains" in Hi-C data, which are the focus of this review. Here, we present a reanalysis of TADs from three "golden-standard" mammalian Hi-C data sets. Despite the prominent presence of TADs in Hi-C heat maps from all studies, we find consistently that regions within these domains are only moderately insulated from their surroundings. Moreover, single-cell Hi-C and superresolution microscopy have revealed that the structure of TADs and the position of their borders can vary from cell to cell. The function of TADs as units of gene regulation may thus require additional aspects, potentially incorporating the mechanism of loop extrusion as well. Recent developments in single-cell and multi-contact genomics and superresolution microscopy assays will be instrumental to link TAD formation and structure to their function in transcriptional regulation. Graphical abstract: Image 1 Highlights: TADs are functional, but context-dependent, units of gene regulation. TAD function relies on the integrity of their borders, which are constituted by ensembles of CTCF binding sites. TADs require Cohesin for their formation through an active loop extrusion mechanism. Insulation of TADs is moderate. Loop extrusion may thus regulate genes itself. Single-cell technologies are providing new insights in TAD structure and function.